Ariosto e il Cardinale. Appunti critici su Freud e lo scrittore creativo (ENTHYMEMA, 2019)
Freud’s attitude towards imagination is ambivalent. On the one hand, he follows a positivist method and considers the products of the imagination as “unproven” and therefore false, on the other hand, however, in describing his clinical cases (The Case of Dora, The Wolf Man ...), he shows himself being a good writer to such an extent as to receive the Goethe prize in 1930. His insisting in many cases on looking for causes was criticized since the 1920’s, for example by L. Vygotsky. However, Freud’s psychoanalysis is not only bound to this context. We can see this aspect from some of his works’ passages which show that imagination and the dream scene constitute a sort of deconstruction apt to reinvent the reality.
Keywords: creativity; imagination; Freud; Tolstoy; Vigotsky